PENERAPAN BUDAYA LITERASI MEMBACA MELALUI CERITA RAKYAT PAPUA DI POJOK BACA SD YPPK ST. PAULUS TUP SOBA KABUPATEN MAPPI - Kornelia Konngerem (Journal of Education Papua Baru, 2026)
Abstract: This study aims to describe the implementation of a reading literacy culture through Papuan folklore in the Reading Corner of SD YPPK St. Paulus Tup Soba, Obaa District, Mappi Regency, South Papua. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews with the principal, teachers, students, parents, and school supervisor, supported by observation and document review. The findings show that Papuan folklore was utilized through the planning of contextual reading materials and the presentation of stories through independent reading, shared reading, storytelling, and competitions. The program encouraged students’ reading interest, as reflected in their enthusiasm for reading, ability to retell the content of stories, and participation in literacy activities both at school and at home. Supporting factors included the principal’s leadership, teacher creativity, parental support, and the cultural relevance of the reading materials. The main constraints were the limited availability of South Papuan folklore books and insufficient funding. These findings highlight the importance of local culture-based literacy for elementary schools in remote areas. Keywords: reading literacy, Papuan folklore, reading corner, elementary school, South Papua   Abstrak: Penelitian ini bertujuan mendeskripsikan implementasi budaya literasi membaca melalui cerita rakyat Papua pada Pojok Baca SD YPPK St. Paulus Tup Soba, Distrik Obaa, Kabupaten Mappi, Papua Selatan. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus. Data diperoleh melalui wawancara mendalam dengan kepala sekolah, guru, siswa, orang tua, dan pengawas sekolah, dilengkapi observasi dan telaah dokumen. Hasil penelitian menunjukkan bahwa pemanfaatan cerita rakyat Papua dilakukan melalui perencanaan bahan bacaan kontekstual, penyajian cerita secara membaca mandiri, membaca bersama, mendongeng, dan lomba. Program ini mendorong peningkatan minat baca siswa yang tampak dari antusiasme membaca, kemampuan menceritakan kembali isi bacaan, dan keterlibatan dalam aktivitas literasi di sekolah maupun rumah. Faktor pendukung meliputi kepemimpinan kepala sekolah, kreativitas guru, dukungan orang tua, dan kedekatan budaya materi bacaan. Kendala utama ialah terbatasnya buku cerita rakyat Papua Selatan dan pendanaan. Temuan ini menegaskan pentingnya literasi berbasis budaya lokal bagi sekolah dasar di daerah terpencil. Kata kunci: literasi membaca, cerita rakyat Papua, pojok baca, sekolah dasar, Papua Selatan